Glass : - Le Bourhis, Eric (Wiley-VCH Verlag, 2008)
This is the first book to discuss the correlation between the performance of industrial processes and practice-relevant properties, such as strength and optical properties. Interdisciplinary in his approach, the author discusses both the science and technology, starting with glass past and present, its structure, and rheology. The sections on properties include mechanical strength and contact resistance, ageing, mechanics of glass processes, the production and control of residual stresses, high-tech producers and current research and development. Applications covered include glazing, packaging, optical glass, glass fibers for reinforcement, and abrasive tools.